The Effect of Firm Size and Good Corporate Governance (GCG) on ESG Risk Ratings (an Empirical Study of Companies Listed on the LQ45 Index of the Indonesia Stock Exchange for the Period 2020-2023) - Muhamad Fauzi; Dwi Jayanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
Companies are now expected to operate in an environmentally friendly and sustainable manner. One indicator of a company’s efforts to mitigate ESG-related risks is its ESG risk rating. However, many companies are still found to have high or even severe ESG risk ratings. This study aims to analyze the effect of firm size and Good Corporate Governance (GCG) scores based on governance disclosure on ESG risk ratings of companies listed in the LQ45 index of the Indonesia Stock Exchange during the 2020–2023 period, with a total sample of 92 observations. This study employs a quantitative approach using secondary data obtained from LQ45 index company factsheets, company financial statements, and sustainability reports. Multiple linear regression analysis is conducted using SPSS version 31. The sample is selected using a purposive sampling method, resulting in 23 companies. The results indicate that both firm size and Good Corporate Governance (GCG) have a significant negative effect on ESG risk ratings.